Adoption Pattern of Solar Cooker in different Agro- ecological Situations of District Ropar (Punjab) - Purva Jaggi and Harinder Singh (Indian Journal of Extension Education, 2015)
Sustainable development requires an organized efforts to develop and defuse new technology appropriate for agriculturalproduction system, renewable energy systems and pollution controls. Energy is one of the vital resources for developmentand survival of mankind. We are fortunate to have abundant sunlight during most part of the year. This untappedrenewable energy could be the best substitute to save conventional fuels used for domestic cooking and at the same timekeep the environment clean. The solar cookers if available can offer a partial solution to multitude of cooking problemsfaced by people of low income. A properly designed and improved cooker if introduced in the market in mass scale cansupplement the cooking energy requirement of several millions of people and reduce deforestation and environmentalproblems associated with the use of fossil fuels. Solar cooker which is safe and simple to operate can satisfactorily be usedfor cooking in the presence of sunshine. The present study has been designed with the objective know the fuelmanagement practices adopted by women in rural areas of three agro-ecological situations of Punjab. The results showedthat the usage varies with the topographical situation. In sub-mountainous area, the usage of electricity and LPG is 24percent and 48per cent respectively whereas the usage of firewood is maximum (88per cent). On the other hand, in the plainarea, the usage of electricity and LPG is 48per cent and 96per cent respectively and that of firewood is 40 per cent only.Electricity which is used by 40per cent households is considered dangerous, expensive and irregular in supply due tofrequent power failure. LPG, which is used by 80per cent households, is also considered as dangerous, having high initialinvestment and limited in supply. Problem reported with the use of kerosene, which is used by 33.33 per cent householdsincludes unpleasant odour, limited supply and adulteration. In case of non- commercial. Firewood which is used by63.33per cent households with maximum usage in the sub- mountainous area , where it is used by 88per cent households isconsidered as unclean, giving smoke, creating health problems, laborious to collect, difficult to procure and difficult tostore. Average saving on fuel per year by the rural households after adopting solar cooker is calculated as a gross reductionof ` 1740 per year and a net saving of 33.33 per cent.